2013
DOI: 10.1002/cphc.201300774
|View full text |Cite
|
Sign up to set email alerts
|

Top‐Hat and Asymmetric Gaussian‐Based Fitting Functions for Quantifying Directional Single‐Molecule Motion

Abstract: Single-molecule fluorescence permits super-resolution imaging, but traditional algorithms for localizing these isolated fluorescent emitters assume stationary point light sources. Proposed here are two fitting functions that achieve similar nanometer-scale localization precision as the traditional symmetric Gaussian function, while allowing, and explicitly accounting for, directed motion. The precision of these methods is investigated through Fisher information analysis, simulation and experiments, and the new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Once more, ignoring this distortion leads to poor localization accuracy, whereas using a PSF model that takes motion into account not only restores the original localization accuracy but also provides information on the instantaneous molecular velocity 200 and additional information on motion models discussed in section 6.5.…”
Section: The Localization Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Once more, ignoring this distortion leads to poor localization accuracy, whereas using a PSF model that takes motion into account not only restores the original localization accuracy but also provides information on the instantaneous molecular velocity 200 and additional information on motion models discussed in section 6.5.…”
Section: The Localization Problemmentioning
confidence: 99%
“…200 Another reason for this blurring, which contains the temporal superresolved image we seek, is that the camera frame rate may be slower than typical frequencies of motion where few photons are released per pixel in turn complicating, in a manner known as aliasing, the “connect-the-dots” problem (Figure 28). …”
Section: The Linking Problemmentioning
confidence: 99%
“…Furthermore, background signals from cellular autofluorescence, diffuse fluorescence from very fast-moving molecules, excess or unwanted fluorophores incorporated into the cell, and camera noise can all worsen the localization precision. In vitro single-molecule experiments achieve high signal-to-noise ratios based on imaging bright, stationary fluorophores in controlled environments, but in live-cell experiments, fluorophores may be dim, background fluorescence can be high, and the molecules of interest generally move during observation [11,6163]. Fluorophore bleaching and blinking can also reduce detectability.…”
Section: Fluorescent Labelsmentioning
confidence: 99%
“…In particularly wet samples, we observed V. cholerae cells swimming rapidly in all directions or spinning in place, presumably when caught on the agarose surface. Alternatively, microfluidic devices may be used to hold cells in place and to keep them nourished during longer or more complex experiments [118,119], and algorithms for handling single-molecule imaging within moving cells are being developed [63]. …”
Section: Sample Considerationsmentioning
confidence: 99%
“…Further data analysis suggested that ToxR acts as a “broom” to clear the DNA, scans for the toxT promotor, and recruits TcpP to activate transcription . Biteen then also gave a summary of several other directions of her recent work, including plasmon‐enhanced fluorescent probes, fluorophore incorporation into proteins via unnatural amino acids, CRISPR/Cas9 technologies for site‐specific fluorescent labeling of genomic sequences, 3D imaging for more accurate diffusion coefficient calculations, and new correlation schemes to track extremely fast particles …”
mentioning
confidence: 99%